Bell's palsy in children: Current treatment patterns in Australia and New Zealand. A PREDICT study. (8th February 2017) - Babl, Franz E; Gardiner, Kaya K; Kochar, Amit; Wilson, Catherine L; George, Shane A; Zhang, Michael; Furyk, Jeremy; Thosar, Deepali; Cheek, John A; Krieser, David; Rao, Arjun S; Borland, Meredith L; et al.
Abstract : Aim: The aetiology and clinical course of Bell's palsy may be different in paediatric and adult patients. There is no randomised placebo controlled trial (RCT) to show effectiveness of prednisolone for Bell's palsy in children. The aim of the study was to assess current practice in paediatric Bell's palsy in Australia and New Zealand Emergency Departments (ED) and determine the feasibility of conducting a multicentre RCT within the Paediatric Research in Emergency Departments International Collaborative (PREDICT). Methods: A retrospective analysis of ED medical records of children less than 18 years diagnosed with Bell's palsy between 1 January, 2012 and 31 December, 2013 was performed. Potential participants were identified from ED information systems using Bell's palsy related search terms. Repeat presentations during the same illness were excluded but relapses were not. Data on presentation, diagnosis and management were entered into an online data base (REDCap). Results: Three hundred and twenty‐three presentations were included from 14 PREDICT sites. Mean age at presentation was 9.0 (SD 5.0) years with 184 (57.0%) females. Most (238, 73.7%) presented to ED within 72 h of symptoms, 168 (52.0%) had seen a doctor prior. In ED, 218 (67.5%) were treated with steroids. Prednisolone was usually prescribed for 9 days at around 1 mg/kg/day, with tapering in 35.7%. Conclusion: Treatment of Bell's palsy in children presenting to Australasian EDs is varied. Prednisolone is commonly used in Australasian EDs, despite lack of high‐level paediatric evidence. The study findings confirm the feasibility of an RCT of prednisolone for Bell's palsy in children.